Challenges and Opportunities of Nontraditional Approaches to Treating Bacterial Infections - Tse, Brian N. (Clin Infect Dis, 2017)
Due to increasing rates of antimicrobial-resistant infections and the current inadequacy of the antibiotic pipeline, there is increasing interest in nontraditional approaches to antibacterial therapies. We define “traditional” agents as small-molecule agents that directly target bacterial components to exert a bacteriostatic or bactericidal effect, and “nontraditional approaches” as antimicrobial therapeutics that work through other means (ie, not a small molecule and/or utilizes a nontraditional target). Due to their atypical features, such therapies may be less susceptible to the emergence of resistance than traditional antibiotics. They include approaches such as monoclonal antibodies, virulence disruptors, immunomodulators, phage therapies, microbiome-based therapies, antibiotic potentiators, and antisense approaches. This article discusses both the developmental and regulatory advantages and challenges associated with each of these technologies. By identifying existing regulatory and developmental gaps, we hope to provide a sense of where focusing resources may provide the greatest impact on successful product development.